Bed bath with soap and water or disposable wet wipes: Patients' experiences and preferences. Issue 11 (12th March 2019) - Veje, Pia L.; Chen, Ming; Jensen, Christian S.; Sørensen, Jan; Primdahl, Jette
Abstract: Aims and objectives: To gain an in‐depth understanding of patients' preferences regarding two bed bath methods: soap and water and disposable wet wipes. Background: Bed baths allow hospitalised, bedridden patients to stay clean and fresh. They serve a number of purposes: health promotion, social propriety and pure pleasure. Traditionally, soap and water have been used for personal hygiene, but in recent years soap and water have increasingly been replaced by the use of disposable wet wipes. Design: A qualitative study with a hermeneutical‐phenomenological approach was chosen to explore and understand patients' experiences of bed bath methods. Methods: Semi‐structured, individual, in‐depth interviews with 16 bedridden patients from three wards were conducted. The software programnvivo was used to structure the transcribed interviews and assist in the initial data analysis. The data were analysed and interpreted within a phenomenological‐hermeneutical framework. COREQ guidelines were used in the preparation of this paper (See Supporting information AppendixS1 ). Results: Four overall themes were identified: "Creating a sense of cleanliness, " "Preferences and concerns in different situations, " "Cleanliness of hands and face" and "Clinical decision‐making about bed bath method." Conclusions: Overall, patients' bed bath preference was for soap and water, but disposable wet wipes were considered a convenient alternative and preferred in certain circumstances, for example, when a patient had pain or diarrhoea. Shared decision‐making regarding bed bath method is recommended. Hands and face had specific requirements. Relevance to clinical practice: Nursing staff should be aware that bedridden patients have varying preferences, and it is important to incorporate the patients' preferences in the development of standards, health policies and clinical guidelines for bed bath practices.